Hemorrhagic shock and tissue injury drive distinct plasma metabolome derangements in swine. Issue 4 (October 2017) - Clendenen, Nathan; Nunns, Geoffrey R.; Moore, Ernest E.; Reisz, Julie A.; Gonzalez, Eduardo; Peltz, Erik; Silliman, Christopher C.; Fragoso, Miguel; Nemkov, Travis; Wither, Matthew J.; Hansen, Kirk; Banerjee, Anirban; et al.
Abstract : BACKGROUND: Tissue injury and hemorrhagic shock induce significant systemic metabolic reprogramming in animal models and critically injured patients. Recent expansions of the classic concepts of metabolomic aberrations in tissue injury and hemorrhage opened the way for novel resuscitative interventions based on the observed abnormal metabolic demands. We hypothesize that metabolic demands and resulting metabolic signatures in pig plasma will vary in response to isolated or combined tissue injury and hemorrhagic shock. METHODS: A total of 20 pigs underwent either isolated tissue injury, hemorrhagic shock, or combined tissue injury and hemorrhagic shock referenced to a sham protocol (n = 5/group). Plasma samples were analyzed by UHPLC-MS. RESULTS: Hemorrhagic shock promoted a hypermetabolic state. Tissue injury alone dampened metabolic responses in comparison to sham and hemorrhagic shock, and attenuated the hypermetabolic state triggered by shock with respect to energy metabolism (glycolysis, glutaminolysis, and Krebs cycle). Tissue injury and hemorrhagic shock had a more pronounced effect on nitrogen metabolism (arginine, polyamines, and purine metabolism) than hemorrhagic shock alone. CONCLUSION: Isolated or combined tissue injury and hemorrhagic shock result in distinct plasma metabolic signatures. These findings indicate that optimized resuscitative interventions in critically ill patients are possible based on identifying the severity of tissue injury and hemorrhage. Abstract : Supplemental digital content is available in the text.